SHARIA PEER-TO-PEER LENDING AND ISLAMIC FINANCIAL LITERACY IN ENHANCING MSMES’ ACCESS TO FINANCING: EVIDENCE FROM MATARAM CITY - Nur Fitri Hidayanti; Sahman Sahman (Universitas Sains Al Qur'an, 2026)
This study examines the influence of Sharia Peer-to-Peer (P2P) lending usage and Islamic financial literacy on MSMEs’ access to financing in Mataram City. MSMEs play a strategic role in economic development; however, limited access to formal financing remains a major challenge. The growth of sharia-based fintech services, particularly P2P lending, provides an alternative funding source, which is expected to be strengthened by adequate Islamic financial literacy. This research employed a quantitative approach using an associative survey design. Data were collected through a structured closed-ended questionnaire measured on a five-point Likert scale and distributed online. A total of 133 MSME actors were selected using purposive sampling. The collected data were analyzed using multiple linear regression with IBM SPSS. The results indicate that Sharia P2P lending usage has a positive and significant effect on MSMEs’ access to financing (β = 0.367, p < 0.001), and Islamic financial literacy also shows a positive and significant effect (β = 0.454, p < 0.001). Simultaneously, both variables significantly influence access to financing (F = 59.734, p < 0.001), with an explanatory power of 47.9% (R² = 0.479). These findings highlight the importance of integrating sharia fintech adoption and strengthening Islamic financial literacy to enhance MSMEs’ financing accessibility. In terms of novelty, this study provides empirical evidence on the simultaneous role of sharia fintech and Islamic financial literacy in improving MSMEs’ access to financing within a developing regional context that remains underexplored in prior studies. This study contributes empirically to the development of Islamic financial inclusion and provides practical implications for policymakers and fintech providers in supporting sustainable MSME growth.